Founders without limits : dual-class stock and the premium tier of the London Stock Exchange / Bobby V. Reddy, University of Cambridge. - Reddy, Bobby V. (International corporate law and financial market regulation., 2021)
Big Tech has flourished on the US public markets in recent years with numerous blue-chip IPOs, from Google and Facebook, to new kids on the block such as Snap, Zoom, and Airbnb. A key trend is the burgeoning use of dual-class stock. Dual-class stock enables founders to divest of equity and generate finance for growth through an IPO, without losing the control they desire to pursue their long-term, market-disrupting visions. Bobby Reddy scrutinises the global history of dual-class stock, evaluates the conceptual and empirical evidence on dual-class stock, and assesses the approach of the London Stock Exchange and ongoing UK regulatory reforms to dual-class stock. A policy roadmap is presented that optimally supports the adoption of dual-class stock while still protecting against its potential abuses, which will more effectively attract high-growth, innovative companies to the UK equity markets, boost the economy, and unleash the true potential of 'founders without limits'.